A new species of Vietnamophryne (Anura: Microhylidae) from Northeastern Vietnam - Ninh, Hoa Thi; Le, Linh Tu Hoang; Bui, Hai Tuan; Nguyen, Huy Quoc; Orlov, Nikolai; Moseyko, Olga Bezman; Le, Manh Van; Nguyen, Sang Ngoc; Hoang, Chung Van; Ziegler, Thomas; Nguyen, Tao Thien (Zootaxa, 2023)
A new species of the genus Vietnamophryne is described from Vietnam on the basis of two specimens collected from Tuyen Quang Province, Northeastern Vietnam. The new species is morphologically most similar to Vietnamophryne occidentalis from Thailand, however, it differs from the latter by having large black blotches in the lower jaw region, and a yellow-orange chest and belly. The genetic distance between the new species and other Vietnamophryne taxa is > 2.13% (16S mtDNA gene fragment). Vietnamophryne aurantifusca sp. nov. can be distinguished from all other species of Vietnamophryne by a combination of the following morphological characteristics: Size medium (SVL 17.6–18.2 mm in males); head wider than long; tympanum medium; finger I longer than half of finger II; dorsal skin relatively smooth with some round nodules, concentrated in the middle of the back, arranged along the length of the back, with a prominent ridge along the spine; Dorsum orangish-brown entirely and paler on margin of back with a small brownish ridge along the spine; sides brownish with creamy patches and orange spots; ventral surface orange, with grey marbling, most intense on the throat, ventral side of arms and thighs, and ventral surfaces of limbs dark grey with some orange spots.